Investigation of carbon contamination in lost foam castings of low carbon steel - Kilic, Oznur; Acar, Serhat; Kisasoz, Alptekin; Guler, Kerem Aitug (FOUNDRY JOURNAL AGENCY, 2018)
Lost foam casting (LFC) process is a special casting method in which polymeric foam patterns with refractory coatings are utilized as a mould component. In this work, four types of foam: expandable polyethylene (EPE), expandable polypropylene (EPP) and expandable polystyrene (EPS) foams with two different densities were employed as pattern materials. LFC and conventional green sand mould casting methods were used to cast a low carbon steel, A216 Grade WCB. Both casting processes were carried out at 1, 580 degrees C. Chemical analysis results showed that the carbon contamination level was high and was influenced by pattern type. Metallographic investigations revealed a significant increase in the percentage of pearlite phase in all LFC samples. Densities of manufactured samples were calculated in order to evaluate porosity of the products. It was determined that the densities of the LFC samples were lower than the green sand mould cast reference sample (RS). Vickers hardness tests were also carried out and increments in hardness values with increased carbon content was observed.
Keywords: lost foam casting (LFC); EPS pattern; EPE pattern; EPP pattern; carbon contamination; MECHANICAL-PROPERTIES; MICROSTRUCTURE; DEGRADATION; MOLD; Metallurgy & Metallurgical Engineering